The Effect of Using Proposed Software by the Students of Instructional Technology to Acquire New Instructional Technology Skills - Dawood Abdulmalek Al-Hidabi; Eissa Mohammed Ali Saleh (University of Science and Technology, Yemen, 2020)
This study investigated the effect of using proposed software by the students of Instructional Technology Department to acquire new instructional technology skills. To achieve the study objectives, the quasi-experimental research with both experimental and control groups was conducted among 40 second-level students of the Instructional Technology Department at Ibb University in the academic year 2018-2019. Participants took pre and post-tests in order to compare the statistical difference before and after the implementation of the proposed software. The research instrument used in this study was an observation card to measure the extent to which students have acquired the new instructional technology skills. After developing a list of new instructional technology skills, building the proposed software and conducting the treatment, the results showed that students in the experimental group were better than the control group in acquiring the new instructional technology skills. These results demonstrated the impact of using the proposed software for acquiring the new instructional technology skills compared to the conventional methods. The study recommended computerizing specialization courses of the Instructional Technology Department, using self-learning methods that would help students acquire better skills so as to improve and develop the learning process.